Bilan spatialisé de la mise en valeur agricole au Sahara algérien - Tayeb Otmane; Yaël Kouzmine (Cybergeo)
The big farms created following the “agricultural development law” (1983) in Algerian Sahara were intended for cereal production, with two objectives: sustain the economic development of the Saharan regions and reduce Algerian food dependency, especially in cereals. Since then, public investments were significant to support this new kind of agricultural development in Algerian arid regions, based on Saudi model. Three decades after the publication of the law, the realizations are still limited. And the farmers, due to the difficult environmental and economic conditions, were constrained to adapt their production towards market gardening under greenhouses alimented by pivots and towards breeding to ensure the durability of their exploitations.